Analysis of CYP450 gene allelic variants can predict ifosfamide toxicity in Mexican paediatric patients. (18th May 2020) - Torres Espíndola, Luz María; Rojo-Serrato, Daniela; Álvaro-Heredia, Antonio; Castillejos López, Manuel de Jesús; de Uña-Flores, Armando; Pérez-García, Martin; Zapata-Tarres, Marta; Cárdenas-Cardos, Rocio; Granados, Julio; Chávez-Pacheco, Juan Luis; Salinas-Lara, Citlaltepetl; de Arellano, Israel Torres-Ramirez; et al.
Abstract: Context: Ifosfamide (IFA) is an effective antineoplastic for solid tumours in children, although it is associated with high levels of systemic toxicity and causes death in some cases. Objective: The aim of this study was to determine whether the presence of certain allelic variants of genes CYP2B6, CYP2C9, CYP3A4 and CYP3A5 increases the risk of toxicity in children with solid tumours treated with ifosfamide. Materials and methods: A total of 131 DNA samples were genotyped by real-time polymerase chain reaction (RT-PCR) using TaqMan probes. Toxicity was assessed using WHO criteria, and survival analysis was performed using Kaplan–Meier curves. Results: The rs3745274 allelic variant in CYP2B6 was associated with haematological toxicity, affecting neutrophils; CYP3A4 variant rs2740574 was also associated with toxicity, affecting both leukocytes and neutrophils. Additionally, the CYP3A5 gene variant rs776746 was found to affect haemoglobin. Conclusions: Our results show that allelic variants rs3745274 ( CYP2B6), rs2740574 ( CYP34) and rs776746 ( CYP3A5) increase the risk for high haematological toxicity. Clinical trial registration: 068/2013